The investigation of luminescence properties of nitride-based heterostructures, containing superlattice - Menkovich, E.A.; Solomonov, A.V.; Tarasov, S.A.; Yurgin, P.A. (Functional Materials, 2014)
The effect of superlattice adding on the luminescence properties of heterostructures based on (Al,In,Ga)N was investigated. It is shown that using structures with two superlattices: the InGaN/InGaN under active region and the AlGaN/GaN as a top p-layer gives the best effect. The elastic stresses on heterointerface of these structure are compensated optimally. As a result they are the most effective and stable functionality.